Perlindungan Konsumen Terhadap Pembelian Produk Impor Melalui Tik Tok Shop - Utami Keliat, Venia; Vincent; Simbolon, Sapriadi (DOKTRINA: JOURNAL OF LAW, 2025)
In an era of increasingly sophisticated technology, aspects of buying and selling have also experienced significant developments along with the progress of the times, namely through online shopping activities on e-commerce platforms, especially for imported products. E-commerce is a buying and selling activity that is carried out boldly (online) by utilizing digital technology. However, on the scale of online buying and selling, the problems that arise tend to be more complex. This is because consumers cannot see the goods directly, but can only assess the product through the description provided by the seller. Therefore, it is important to understand how consumer protection is regulated in e-commerce in Indonesia and the form of legal protection for consumers on platforms such as TikTok Shop. This study uses a normative legal research method. The regulation of consumer protection in e-commerce is regulated in Law Number 8 of 1999 concerning Consumer Protection and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE). Settlement of peace that arises in an effort to protect consumers can be done through litigation or non-litigation. If the settlement cannot be resolved peacefully, consumers have the right to file a lawsuit in court.